2015
DOI: 10.1038/srep13977
|View full text |Cite
|
Sign up to set email alerts
|

Titania may produce abiotic oxygen atmospheres on habitable exoplanets

Abstract: The search for habitable exoplanets in the Universe is actively ongoing in the field of astronomy. The biggest future milestone is to determine whether life exists on such habitable exoplanets. In that context, oxygen in the atmosphere has been considered strong evidence for the presence of photosynthetic organisms. In this paper, we show that a previously unconsidered photochemical mechanism by titanium (IV) oxide (titania) can produce abiotic oxygen from liquid water under near ultraviolet (NUV) lights on th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…If (11) or (13) exceeds the atmospheric O 2 sinks for Earth-like planets, oxygen can build up in the atmosphere and produce an ozone layer (Catling and Kasting, 2017a). A number of studies have been conducted that pertain to the production of abiotic O 2 and O 3 in the atmosphere due to the photolysis of H 2 O and CO 2 by XUV radiation Pierrehumbert, 2013, 2014;Tian et al, 2014;Harman et al, 2015;Narita et al, 2015;Gao et al, 2015). Hence, the detection of O 2 and O 3 at high levels in exoplanetary atmospheres opens up the possibility of a "false positive", corresponding to the apparent detection of a biosignature despite it not being produced by biological activity.…”
Section: A Evaporation Of Oceans and Buildup Of Oxygenmentioning
confidence: 99%
“…If (11) or (13) exceeds the atmospheric O 2 sinks for Earth-like planets, oxygen can build up in the atmosphere and produce an ozone layer (Catling and Kasting, 2017a). A number of studies have been conducted that pertain to the production of abiotic O 2 and O 3 in the atmosphere due to the photolysis of H 2 O and CO 2 by XUV radiation Pierrehumbert, 2013, 2014;Tian et al, 2014;Harman et al, 2015;Narita et al, 2015;Gao et al, 2015). Hence, the detection of O 2 and O 3 at high levels in exoplanetary atmospheres opens up the possibility of a "false positive", corresponding to the apparent detection of a biosignature despite it not being produced by biological activity.…”
Section: A Evaporation Of Oceans and Buildup Of Oxygenmentioning
confidence: 99%
“…This study is not the first to point out that enthusiasm about extraterrestrial life is misplaced when all that is found is a simple compound. Earlier this year, Narita et al [ 35 ] made the same point in connection to molecular oxygen. Fluid water is very special, but our beautiful Earth-Moon-Double-Planet-System has more aspects that are special.…”
Section: Discussionmentioning
confidence: 81%
“…When more realistic assumptions of volcanic outgassing were used, their O 2 abundances dropped to a few parts per million. As another possible abiotic mechanism for O 2 buildup, Léger et al ( 2011 ) discussed the efficacy of known catalysts for abiotic photogeneration of O 2 from water-splitting on a planetary surface but concluded that it was highly unlikely to occur on a habitable planet, although a subsequent study argued that this may be possible, if significantly large areas of the planet supported a catalyst (Narita et al, 2015 ). Another possible mechanism, O 2 derived from the release of H 2 O 2 during the melt of a pole-to-pole ice-covered Snowball Earth (Liang et al, 2006 ), also only produces abundances of a few parts per million of O 2 in the lower atmosphere.…”
Section: Oxygen Biosignature False Positivesmentioning
confidence: 99%